Cytolytic Effects of Newcastle Disease Virus Strain Af2240 on Dbtrg.05mg and U-87mg Brain Tumor Cell Lines - Saeed, Rola Ali (2008)
Newcastle disease virus (NDV) is a potential oncolytic agent as it can replicate up to 10,000 times better in human cancer cells than in most normal human cells. Several strains of NDV were reported to induce cytolysis to various cancerous cell lines. In this study, the cytolytic effects of local strain NDV AF2240 toward DBTRG.05MG (glioblastoma multiform) and U-87MG (anaplastic astrocytoma) cell lines were determined using microtetrazolium assay (MTT) for both monolayer and co-culture methods. The value of (IC50) inhibition concentration, fifty percent at which the titer of NDV as hemagglutination units (HAU) that reduce 50% of cell population as compared to the untreated control was determined after 72 hours. TheIC50 values for cytolytic effects of NDV strain AF2240 on DBTRG.05MG cell line were 955 HAU/ml and 460 HAU/ml for the monolayer and co-culture methods, respectively. For U- 87MG cell line, the IC50 values were 380 HAU/ml and 52 HAU\ml for monolayer and co-culture methods, respectively. No significant cytolytic effect was observed on normal HCN-2 and 3T3 cell lines at the same titre used in the brain tumor cell lines. The cell proliferation rate of treated brain tumor cell lines was reduced significantly with time and titration of the virus as compared to the untreated control. It was confirmed that the mode of cell death in response to infection by NDV strain AF2240 on brain tumor cell lines was by apoptosis. Morphological features of apoptosis were observed by Phase Contrast Microscopy, Fluorescence Microscopy (Acridine Orange (AO) and Propidium Iodide (PI) staining) and Transmission Electron Microscopy. Features observed included chromatin condensation and margination along the inner nuclear membrane, cytoplasmic condensation, and membrane blebbing without disintegration of the cellular membrane. These were further confirmed with DNA laddering in agarose gel electrophoresis assay and terminal deoxyribonucleotide transferase-mediated dUTP-X nick end-labeling staining (TUNEL) assay. However, analysis of the cellular DNA content using PI showed that the virus caused an increase in sub-G1 region. The apoptosis peaks (sub-G1) found in DBTRG.05MG cells treated with NDV strain AF2240 were 18.40 and 37.40% for 24 and 48 hours, respectively whereas in U-87MG cells treated with NDV strain AF2240 the peaks were 10.29 and 19.45% for 24 and 48 hours, respectively. Early apoptosis was also observed by annexin V flow cytometry method. The amounts of apoptotic cells were 3.7 and 4.26% for DBTRG.05MG cells and U-87MG cells 6 hours post-inoculation, respectively. It was concluded that NDV strain AF2240 is a potent antitumor agent and the mode of cell death induced by this virus is apoptosis.